From Dickens to Dracula : Gothic, economics, and Victorian fiction - Houston, Gail Turley, 1950- (Cambridge University Press, 2005)
Gail Turley Houston examines how the language and imagery of economics are transformed in Gothic fiction, and traces literary and uncanny elements in economic writings of the period. This stimulating interdisciplinary book reveals that the worlds of Victorian economics and Gothic fiction, seemingly separate, actually complemented and enriched each other.
Keywords: Dickens, Charles, -- 1812-1870 -- Knowledge -- Economics.; Stoker, Bram, -- 1847-1912. -- Dracula.; Dracula, -- Count (Fictitious character); Dickens, Charles, -- 1812-1870 -- Et l'aspect économique.; Stoker, Bram, -- 1847-1912 -- Dracula.; Dickens, Charles, -- 1812-1870; Dracula (Stoker, Bram); English fiction -- 19th century -- History and criticism.; Economics in literature.; Economics and literature -- Great Britain -- History -- 19th century.; Financial crises -- Great Britain -- History -- 19th century.; Horror tales, English -- History and criticism.; Gothic revival (Literature) -- Great Britain.; Financial crises in literature.; Money in literature.; Dracula (Personnage fictif); Économie politique et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Roman anglais -- 19e siècle -- Histoire et critique.; Économie politique dans la littérature.; Krach dans la littérature.; Argent dans la littérature.; Littérature frénétique -- Grande-Bretagne.; Récits d'horreur anglais -- Histoire et critique.; Krachs -- Grande-Bretagne -- Historie -- 19e siècle.; Krachs -- Grande-Bretagne -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Economics; Economics and literature; Economics in literature; English fiction; Financial crises; Financial crises in literature; Gothic revival (Literature); Horror tales, English; Money in literature; Great Britain; Victoriaanse tijd.; Gothic novel.; 1800-1899; Electronic books.; Criticism, interpretation, etc.; History